The use of small group discussions (SGD) in pharmacology classes as a component of the formation of professionally oriented knowledge competence - Kucher, T. V.; Кучер, Тетяна Володимирівна (Liverpool : Cognum Publishing House, 2023)
Abstract: The main task of higher education at the present stage is to train students who are able not only to obtain certain theoretical knowledge but also to master the skills of applying the acquired knowledge in specific situations.
Keywords: Pharmacology; technique of group classes; problem-based learning; small group discussions; situational tasks; structural logic diagrams; Step-by-step Discussions